ENERGY RESOURCES AS FACTOR OF NEW INTERESTS AND OPPORTUNITIES IN THE RELATIONS BETWEEN THE EU AND CA (International relations and international law Journal, 2016)
The article analyses problems of the European Union and Central Asia cooperation concerning problem of energy resources. The topic is very actual for intensifi cation of cooperation between these two regions. Author considers an importance of energy resources of the Caspian Sea for the security of the European Union.
Keywords: Central Asia; European Union; oil; energy resources